Working in partnership: The role of Peer Assisted Study Sessions in engaging the Citizen Scholar. (November 2019) - McIntosh, Emily A
This article argues that peer learning, specifically Peer Assisted Study Sessions, supported by academic tutors, is a valuable part of the agenda to emphasise the social mission of higher education. This study draws on data collected at two time points from respondents who were trained as Peer Assisted Study Sessions leaders. The data reveal that peer learning interventions nurture specific proficiencies and attributes of the Citizen Scholar, particularly creativity and innovation, design thinking and resilience. This study focuses on how Peer Assisted Study Sessions leader respondents conceptualise and articulate their own learning, relating it to the development of these specific proficiencies and attributes. It also offers insight into how Peer Assisted Study Sessions leaders foster the skills of citizen scholarship for those participating in their sessions.